231k views
4 votes
If f (x) = – 4x3 + 2x2 – 1, find f (– 1)

2 Answers

4 votes

Answer:


f(-1)=5

Explanation:

We know that the equation is


f(x)=-4x^3+2x^2-1

We can then plug -1 in for x


f(-1)=-4(-1)^3+2(-1)^2-1\\\\f(-1)=-4(-1)+2(1)-1\\\\f(-1)=4+2-1\\\\f(-1)=5

User Spzvtbg
by
5.0k points
3 votes

ANSWER


f( - 1) = 5

EXPLANATION

The given function is


f(x) = - 4 {x}^(3) + 2 {x}^(2) - 1

We substitute x=-1 to obtain:


f( - 1) = - 4 {( - 1)}^(3) + 2 {( - 1)}^(2) - 1

We simplify to obtain;


f( - 1) = 4 + 2 - 1

.

This evaluates to


f( - 1) = 5

User Finferflu
by
5.1k points